Role of Fair Value Accounting in Shaping Investor Confidence: Primary Evidence from Kathmandu Valley - Subedi, Purushottam; Kumar, Alok (Darul Yasin Al Sys, 2025)
Fair Value Accounting (FVA) plays a critical role in financial reporting by aiming to reflect the accurate economic value of assets and liabilities. However, its influence on investor confidence remains underexplored in emerging economies such as Nepal. This study examines investor perceptions of FVA and investigates the relationship between key accounting dimensions and investor confidence. Employing a cross-sectional, quantitative research design, data were collected via a structured questionnaire from 385 respondents, including BBS and MBS students, freelance investors, and teaching faculty using convenience sampling within the Kathmandu Valley. The results reveal significant positive relationships between FVA components and investor confidence. Specifically, transparency, valuation reliability, and frequent revaluation significantly enhance investor confidence, whereas volatility does not show a meaningful effect. The regression model accounted for over 54% of the variance in investor confidence. The study concludes that enhancing the clarity, reliability, and frequency of fair value reporting can substantially improve investor trust in Nepal’s financial markets, offering practical implications for policymakers, regulators, and accounting professionals.